A kind of high-density knitted fabric with anti-pilling properties and its production process

By treating polyester filaments and spandex filaments with modified dipping agents, combined with knitting circular knitting and shaping treatments, the existing knitted fabrics have solved the difficult-to-coordinate problems in anti-pilling, anti-fouling and bursting strength, achieving improved performance. Improve coordination, balance and stability.

CN118957984BActive Publication Date: 2025-01-17DEPUJIA TECHNOLOGY DEVELOPMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411451204.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-17
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

Existing knitted fabrics are difficult to coordinate and balance in terms of pilling resistance, anti-fouling properties and top-breaking strength, and have poor performance stability under sun exposure and water washing conditions.

Method used

Polyester filament and spandex filament are treated with modified dipping agent. The modified dipping agent is composed of silane coupling agent, citric acid, sodium alginate solution, yttrium nitrate solution and modified nano-titanium dioxide. It is woven through ultrasonic dipping and circular knitting machine. Finally, drying and stenter shaping are carried out.

Benefits of technology

It achieves a coordinated and balanced improvement in the anti-pilling performance, anti-fouling performance and bursting strength of knitted fabrics, and maintains good performance stability under sun exposure and water washing conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of knitted fabrics, and in particular to a high-density knitted fabric with anti-pilling properties and a production process thereof, comprising the following steps: immersing polyester filaments and spandex filaments in a sufficient amount of a modified immersion agent for ultrasonic immersion treatment, taking out and drying after the immersion, and obtaining the immersion-modified polyester filaments and the immersion-modified spandex filaments respectively. The high-density knitted fabric obtained by the invention has improved anti-pilling performance, anti-fouling performance, high-density performance and bursting strength, and the product has an obvious performance stability effect under the conditions of sun exposure and water washing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of knitted fabrics, and in particular to an anti-pilling high-density knitted fabric and a production process thereof. Background Art

[0002] Knitted fabrics are soft, moisture-absorbent and breathable, have excellent elasticity and extensibility, and are easy to produce. Knitted clothing is comfortable to wear, fits the body, has no tightness, and can fully reflect the curves of the human body. Knitted fabrics are made by using knitting needles to bend yarns into loops and string them together. They are divided into warp knitted fabrics and weft knitted fabrics.

[0003] The existing knitted fabric has poor bursting strength, and it is difficult to coordinate and balance the anti-pilling and anti-fouling properties of the product with the bursting strength. In addition, the performance stability of the product is significantly reduced under the conditions of sun exposure and water washing, which limits the use efficiency of the product. Based on this, the present invention further improves it. Summary of the invention

[0004] In view of the defects of the prior art, the purpose of the present invention is to provide an anti-pilling high-density knitted fabric and a production process thereof to solve the problems raised in the above background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution:

[0006] The present invention provides a production process of anti-pilling high-density knitted fabric, comprising the following steps:

[0007] Step 1: Preparation of modified impregnating agent:

[0008] (1) Weigh the raw materials according to weight:

[0009] 2-5 parts of silane coupling agent KH560, 4-7 parts of regulator, 1-3 parts of yttrium nitrate solution, 2-4 parts of citric acid, 5-8 parts of sodium alginate solution and 3-5 parts of modified nano titanium dioxide;

[0010] (2) Add silane coupling agent KH560, citric acid and yttrium nitrate solution to the sodium alginate solution, then add the regulator and modified nano titanium dioxide, continue to stir and mix thoroughly, and obtain a modified impregnating agent;

[0011] Step 2: immersing the polyester filament and the spandex filament into a sufficient amount of a modified immersion agent for ultrasonic immersion treatment, and after the immersion is completed, taking out and drying to obtain the immersion-modified polyester filament and the immersion-modified spandex filament respectively;

[0012] Step 3: The modified polyester filament and the modified spandex filament are used as warp and weft respectively, and the warp and weft are woven by a circular knitting machine to obtain a knitted fabric; the linear density of the warp is 9.8 tex, and the linear density of the weft is 8.5 tex;

[0013] Step 4: Dry and shape the knitted fabric first, and then stretch and shape it on a shaping machine to obtain a high-density knitted fabric that is anti-pilling.

[0014] Preferably, the ultrasonic power of the ultrasonic immersion treatment in step 2 is 400-500W, and the ultrasonic time is 20-30min;

[0015] The drying and shaping time in step 4 is 20-25s, and the drying temperature is 135-145°C; the stentering and shaping temperature is 170-175°C, and the vehicle speed is 25-30m / min.

[0016] Preferably, the mass fraction of the yttrium nitrate solution is 2-5%; the mass fraction of the sodium alginate solution is 3-6%.

[0017] Preferably, the production process of the regulator is:

[0018] S01: Mix nano mica powder and chitosan solution with a mass fraction of 3-5% in a sodium dodecylbenzene sulfonate solution with a mass fraction of 5% to obtain a nano mica powder solution;

[0019] The mass ratio of nano-mica powder, chitosan solution and sodium dodecylbenzene sulfonate solution is (2-5):3:(5-8);

[0020] S02: 4-7 parts of glass fiber, 2-5 parts of lanthanum nitrate solution and 1-3 parts of carboxymethyl cellulose are mixed and ball-milled by weight, and then filtered and dried to obtain modified glass fiber. The ball-milling speed is 1500r / min and the ball-milling is performed for 1h;

[0021] S03: 5-8 parts of nano-mica powder liquid, 1-3 parts of silane coupling agent KH550 and 2-5 parts of modified glass fiber are blended and ball-milled by weight at a ball-milling speed of 1000-1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a regulator.

[0022] Preferably, the mass fraction of the lanthanum nitrate solution is 3-6%.

[0023] Preferably, the production process of the modified nano titanium dioxide is:

[0024] S11: preheating the nano titanium dioxide at 55-60° C. for 10-15 minutes, and then treating it in a proton irradiation box for 10-15 minutes, with an irradiation power of 350-400 W. After the irradiation is completed, irradiated nano titanium dioxide is obtained;

[0025] S12: stirring the irradiated nano titanium dioxide and the modified liquid at a weight ratio of 2:5 for modification treatment, filtering and drying after the stirring is completed to obtain modified nano titanium dioxide.

[0026] Preferably, the stirring speed of the stirring modification treatment is 450-550 r / min, and the stirring time is 35-45 min.

[0027] Preferably, the modified liquid comprises the following raw materials in parts by weight:

[0028] 2-5 parts of halloysite, 1-3 parts of nano silica sol, 4-7 parts of sodium silicate solution, 2-3 parts of flaky talc powder and 2-4 parts of dopamine hydrochloride solution.

[0029] Preferably, the mass fraction of the sodium silicate solution is 2-5%; the mass fraction of the dopamine hydrochloride solution is 3-6%.

[0030] The invention also provides an anti-pilling high-density knitted fabric, which is produced by the production process of the anti-pilling high-density knitted fabric.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The high-density knitted fabric of the present invention is prepared by respectively immersing polyester filaments and spandex filaments into a sufficient amount of modified impregnating agent for immersion improvement, and then knitting large circular machine weaving and drying and shaping are carried out, and then the fabric is stretched and shaped on a shaping machine. In the preparation of the modified impregnating agent, silane coupling agent KH560 is used to blend citric acid, sodium alginate solution and yttrium nitrate solution. Through the coordination between the raw materials, the impregnation improvement effect of the polyester filaments and the spandex filaments is enhanced. At the same time, the added regulator and modified nano titanium dioxide are coordinated and synergistic with each other, so that the obtained high-density knitted fabric has improved anti-pilling performance, anti-fouling performance, high density performance and bursting strength, and the product has obvious performance stability under the conditions of sun exposure and water washing. The regulator adopts nano mica powder to cooperate with chitosan solution and sodium dodecylbenzene sulfonate solution. Through the coordination between the raw materials, the interface and compatibility between the raw materials are enhanced. At the same time, the nano mica powder is distributed in a lamellar structure system to enhance the body The interfacial effect of the system, glass fiber, lanthanum nitrate solution and carboxymethyl cellulose are blended and ball-milled to obtain lanthanum-doped glass fiber with needle-like activity, which enhances the reinforcement effect of the needle-like structure, and then through the coordination between nano mica powder liquid and silane coupling agent KH550, the coordination effect between the product raw materials is enhanced, thereby better impregnation improvement of polyester filaments and spandex filaments, and the knitting connection effect between polyester filaments and spandex filaments is enhanced, thereby improving the high density and other performance effects of the product; the modified nano titanium dioxide is preheated and irradiated to stimulate its active efficiency, and then improved by the modifying liquid. The modifying liquid adopts the coordination between halloysite, nano silica sol, sodium silicate solution, flaky talcum powder and dopamine hydrochloride solution. Through the structural system of halloysite and the combination of flaky talcum powder, the reinforcing regulator is coordinated, and the modified impregnating agent obtained can better improve the polyester filaments and spandex filaments, thereby further improving the performance of the product. DETAILED DESCRIPTION

[0033] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] A production process of an anti-pilling high-density knitted fabric of this embodiment comprises the following steps:

[0035] Step 1: Preparation of modified impregnating agent:

[0036] (1) Weigh the raw materials according to weight:

[0037] 2-5 parts of silane coupling agent KH560, 4-7 parts of regulator, 1-3 parts of yttrium nitrate solution, 2-4 parts of citric acid, 5-8 parts of sodium alginate solution and 3-5 parts of modified nano titanium dioxide;

[0038] (2) Add silane coupling agent KH560, citric acid and yttrium nitrate solution to the sodium alginate solution, then add the regulator and modified nano titanium dioxide, continue to stir and mix thoroughly, and obtain a modified impregnating agent;

[0039] Step 2: immersing the polyester filament and the spandex filament into a sufficient amount of a modified immersion agent for ultrasonic immersion treatment, and after the immersion is completed, taking out and drying to obtain the immersion-modified polyester filament and the immersion-modified spandex filament respectively;

[0040] Step 3: The modified polyester filament and the modified spandex filament are used as warp and weft respectively, and the warp and weft are woven by a circular knitting machine to obtain a knitted fabric; the linear density of the warp is 9.8 tex, and the linear density of the weft is 8.5 tex;

[0041] Step 4: Dry and shape the knitted fabric first, and then stretch and shape it on a shaping machine to obtain a high-density knitted fabric that is anti-pilling.

[0042] In step 2 of this embodiment, the ultrasonic power of the ultrasonic immersion treatment is 400-500W, and the ultrasonic time is 20-30min;

[0043] The drying and shaping time in step 4 is 20-25s, and the drying temperature is 135-145°C; the stentering and shaping temperature is 170-175°C, and the vehicle speed is 25-30m / min.

[0044] The mass fraction of the yttrium nitrate solution in this embodiment is 2-5%; the mass fraction of the sodium alginate solution is 3-6%.

[0045] The production process of the regulator of this embodiment is:

[0046] S01: Mix nano mica powder and chitosan solution with a mass fraction of 3-5% in a sodium dodecylbenzene sulfonate solution with a mass fraction of 5% to obtain a nano mica powder solution;

[0047] The mass ratio of nano-mica powder, chitosan solution and sodium dodecylbenzene sulfonate solution is (2-5):3:(5-8);

[0048] S02: 4-7 parts of glass fiber, 2-5 parts of lanthanum nitrate solution and 1-3 parts of carboxymethyl cellulose are mixed and ball-milled by weight, and then filtered and dried to obtain modified glass fiber. The ball-milling speed is 1500r / min and the ball-milling is performed for 1h;

[0049] S03: 5-8 parts of nano-mica powder liquid, 1-3 parts of silane coupling agent KH550 and 2-5 parts of modified glass fiber are blended and ball-milled by weight at a ball-milling speed of 1000-1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a regulator.

[0050] The mass fraction of the lanthanum nitrate solution of the present embodiment is 3-6%.

[0051] The production process of modified nano titanium dioxide in this embodiment is:

[0052] S11: preheating the nano titanium dioxide at 55-60° C. for 10-15 minutes, and then treating it in a proton irradiation box for 10-15 minutes, with an irradiation power of 350-400 W. After the irradiation is completed, irradiated nano titanium dioxide is obtained;

[0053] S12: stirring the irradiated nano titanium dioxide and the modified liquid at a weight ratio of 2:5 for modification treatment, filtering and drying after the stirring is completed to obtain modified nano titanium dioxide.

[0054] The stirring speed of the stirring modification treatment in this embodiment is 450-550 r / min, and the stirring time is 35-45 min.

[0055] The modified solution of this embodiment includes the following raw materials in parts by weight:

[0056] 2-5 parts of halloysite, 1-3 parts of nano silica sol, 4-7 parts of sodium silicate solution, 2-3 parts of flaky talc powder and 2-4 parts of dopamine hydrochloride solution.

[0057] The mass fraction of the sodium silicate solution in this embodiment is 2-5%; the mass fraction of the dopamine hydrochloride solution is 3-6%.

[0058] This embodiment also provides an anti-pilling high-density knitted fabric, which is produced by the production process of the anti-pilling high-density knitted fabric.

[0059] Embodiment 1: A production process of an anti-pilling high-density knitted fabric, comprising the following steps:

[0060] Step 1: Preparation of modified impregnating agent:

[0061] (1) Weigh the raw materials according to weight:

[0062] 2 parts of silane coupling agent KH560, 4 parts of regulator, 1 part of yttrium nitrate solution, 2 parts of citric acid, 5 parts of sodium alginate solution and 3 parts of modified nano titanium dioxide;

[0063] (2) Add silane coupling agent KH560, citric acid and yttrium nitrate solution to the sodium alginate solution, then add the regulator and modified nano titanium dioxide, continue to stir and mix thoroughly, and obtain a modified impregnating agent;

[0064] Step 2: immersing the polyester filament and the spandex filament into a sufficient amount of a modified immersion agent for ultrasonic immersion treatment, and after the immersion is completed, taking out and drying to obtain the immersion-modified polyester filament and the immersion-modified spandex filament respectively;

[0065] Step 3: The modified polyester filament and the modified spandex filament are used as warp and weft respectively, and the warp and weft are woven by a circular knitting machine to obtain a knitted fabric; the linear density of the warp is 9.8 tex, and the linear density of the weft is 8.5 tex;

[0066] Step 4: Dry and shape the knitted fabric first, and then stretch and shape it on a shaping machine to obtain a high-density knitted fabric that is anti-pilling.

[0067] The ultrasonic power of the ultrasonic immersion treatment in step 2 of this embodiment is 400W, and the ultrasonic time is 20min;

[0068] The drying and shaping time in step 4 is 20 seconds, and the drying temperature is 135° C.; the stentering and shaping temperature is 170° C., and the vehicle speed is 25 m / min.

[0069] The mass fraction of the yttrium nitrate solution in this embodiment is 2%; the mass fraction of the sodium alginate solution is 3%.

[0070] The production process of the regulator of this embodiment is:

[0071] S01: Mix the nano-mica powder and 3% chitosan solution in 5% sodium dodecylbenzene sulfonate solution to obtain a nano-mica powder solution;

[0072] The mass ratio of nano-mica powder, chitosan solution and sodium dodecylbenzene sulfonate solution is 2:3:5;

[0073] S02: 4 parts of glass fiber, 2 parts of lanthanum nitrate solution and 1 part of carboxymethyl cellulose were mixed and ball-milled by weight, and then filtered and dried to obtain modified glass fiber. The ball-milling speed was 1500 r / min and the ball-milling was performed for 1 hour.

[0074] S03: 5 parts of nano-mica powder liquid, 1 part of silane coupling agent KH550 and 2 parts of modified glass fiber are blended and ball-milled by weight at a ball-milling speed of 1000 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a regulator.

[0075] The mass fraction of the lanthanum nitrate solution in this embodiment is 3%.

[0076] The production process of modified nano titanium dioxide in this embodiment is:

[0077] S11: preheating the nano-titanium dioxide at 55° C. for 10 minutes, and then treating it in a proton irradiation box for 10 minutes, with an irradiation power of 350 W. After the irradiation is completed, irradiated nano-titanium dioxide is obtained;

[0078] S12: stirring the irradiated nano titanium dioxide and the modified liquid at a weight ratio of 2:5 for modification treatment, filtering and drying after the stirring is completed to obtain modified nano titanium dioxide.

[0079] The stirring speed of the stirring modification treatment in this embodiment is 450 r / min, and the stirring time is 35 min.

[0080] The modified solution of this embodiment includes the following raw materials in parts by weight:

[0081] 2 parts of halloysite, 1 part of nano silica sol, 4 parts of sodium silicate solution, 2 parts of flaky talc and 2 parts of dopamine hydrochloride solution.

[0082] The mass fraction of the sodium silicate solution in this embodiment is 2%; the mass fraction of the dopamine hydrochloride solution is 3%.

[0083] This embodiment also provides an anti-pilling high-density knitted fabric, which is produced by the production process of the anti-pilling high-density knitted fabric.

[0084] Embodiment 2: A production process of an anti-pilling high-density knitted fabric, comprising the following steps:

[0085] Step 1: Preparation of modified impregnating agent:

[0086] (1) Weigh the raw materials according to weight:

[0087] 5 parts of silane coupling agent KH560, 7 parts of regulator, 3 parts of yttrium nitrate solution, 4 parts of citric acid, 8 parts of sodium alginate solution and 5 parts of modified nano titanium dioxide;

[0088] (2) Add silane coupling agent KH560, citric acid and yttrium nitrate solution to the sodium alginate solution, then add the regulator and modified nano titanium dioxide, continue to stir and mix thoroughly, and obtain a modified impregnating agent;

[0089] Step 2: immersing the polyester filament and the spandex filament into a sufficient amount of a modified immersion agent for ultrasonic immersion treatment, and after the immersion is completed, taking out and drying to obtain the immersion-modified polyester filament and the immersion-modified spandex filament respectively;

[0090] Step 3: The modified polyester filament and the modified spandex filament are used as warp and weft respectively, and the warp and weft are woven by a circular knitting machine to obtain a knitted fabric; the linear density of the warp is 9.8 tex, and the linear density of the weft is 8.5 tex;

[0091] Step 4: Dry and shape the knitted fabric first, and then stretch and shape it on a shaping machine to obtain a high-density knitted fabric that is anti-pilling.

[0092] The ultrasonic power of the ultrasonic immersion treatment in step 2 of this embodiment is 500W, and the ultrasonic time is 30min;

[0093] The drying and shaping time in step 4 is 25s, and the drying temperature is 145°C; the stentering and shaping temperature is 175°C, and the vehicle speed is 30m / min.

[0094] The mass fraction of the yttrium nitrate solution in this embodiment is 5%; the mass fraction of the sodium alginate solution is 6%.

[0095] The production process of the regulator of this embodiment is:

[0096] S01: Mix the nano-mica powder and 5% by mass chitosan solution in 5% by mass sodium dodecylbenzene sulfonate solution to obtain a nano-mica powder solution;

[0097] The mass ratio of nano-mica powder, chitosan solution and sodium dodecylbenzene sulfonate solution is 5:3:8;

[0098] S02: 7 parts of glass fiber, 5 parts of lanthanum nitrate solution and 3 parts of carboxymethyl cellulose were mixed and ball-milled by weight, and then filtered and dried to obtain modified glass fiber. The ball-milling speed was 1500 r / min and the ball-milling was performed for 1 hour.

[0099] S03: 8 parts of nano-mica powder liquid, 3 parts of silane coupling agent KH550 and 5 parts of modified glass fiber are blended and ball-milled by weight at a ball-milling speed of 1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a regulator.

[0100] The mass fraction of the lanthanum nitrate solution of the present embodiment is 6%.

[0101] The production process of modified nano titanium dioxide in this embodiment is:

[0102] S11: preheating the nano-titanium dioxide at 60° C. for 15 minutes, and then treating it in a proton irradiation box for 15 minutes, with an irradiation power of 400 W. After the irradiation is completed, irradiated nano-titanium dioxide is obtained;

[0103] S12: stirring the irradiated nano titanium dioxide and the modified liquid at a weight ratio of 2:5 for modification treatment, filtering and drying after the stirring is completed to obtain modified nano titanium dioxide.

[0104] The stirring speed of the stirring modification treatment in this embodiment is -550r / min, and the stirring time is 45min.

[0105] The modified solution of this embodiment includes the following raw materials in parts by weight:

[0106] 5 parts of halloysite, 3 parts of nano silica sol, 7 parts of sodium silicate solution, 3 parts of flaky talc and 4 parts of dopamine hydrochloride solution.

[0107] The mass fraction of the sodium silicate solution in this embodiment is 5%; the mass fraction of the dopamine hydrochloride solution is 6%.

[0108] This embodiment also provides an anti-pilling high-density knitted fabric, which is produced by the production process of the anti-pilling high-density knitted fabric.

[0109] Embodiment 3: A production process of an anti-pilling high-density knitted fabric, comprising the following steps:

[0110] Step 1: Preparation of modified impregnating agent:

[0111] (1) Weigh the raw materials according to weight:

[0112] 3.5 parts of silane coupling agent KH560, 5.5 parts of regulator, 2 parts of yttrium nitrate solution, 3 parts of citric acid, 6.5 parts of sodium alginate solution and 4 parts of modified nano titanium dioxide;

[0113] (2) Add silane coupling agent KH560, citric acid and yttrium nitrate solution to the sodium alginate solution, then add the regulator and modified nano titanium dioxide, continue to stir and mix thoroughly, and obtain a modified impregnating agent;

[0114] Step 2: immersing the polyester filament and the spandex filament into a sufficient amount of a modified immersion agent for ultrasonic immersion treatment, and after the immersion is completed, taking out and drying to obtain the immersion-modified polyester filament and the immersion-modified spandex filament respectively;

[0115] Step 3: The modified polyester filament and the modified spandex filament are used as warp and weft respectively, and the warp and weft are woven by a circular knitting machine to obtain a knitted fabric; the linear density of the warp is 9.8 tex, and the linear density of the weft is 8.5 tex;

[0116] Step 4: Dry and shape the knitted fabric first, and then stretch and shape it on a shaping machine to obtain a high-density knitted fabric that is anti-pilling.

[0117] In step 2 of this embodiment, the ultrasonic power of the ultrasonic immersion treatment is 450W, and the ultrasonic time is 25min;

[0118] The drying and shaping time in step 4 is 22s, and the drying temperature is 140°C; the stentering and shaping temperature is 172°C, and the vehicle speed is 27.5m / min.

[0119] The mass fraction of the yttrium nitrate solution in this embodiment is 3.5%; the mass fraction of the sodium alginate solution is 4.5%.

[0120] The production process of the regulator of this embodiment is:

[0121] S01: Mix nano mica powder and 4% chitosan solution in 5% sodium dodecylbenzene sulfonate solution to obtain nano mica powder solution;

[0122] The mass ratio of nano-mica powder, chitosan solution and sodium dodecylbenzene sulfonate solution is 3.5:3:6.5;

[0123] S02: 5.5 parts of glass fiber, 3.5 parts of lanthanum nitrate solution and 2 parts of carboxymethyl cellulose were mixed and ball-milled by weight, and then filtered and dried to obtain modified glass fiber. The ball-milling speed was 1500 r / min and the ball-milling was performed for 1 hour.

[0124] S03: 6.5 parts of nano-mica powder liquid, 2 parts of silane coupling agent KH550 and 3.5 parts of modified glass fiber are blended and ball-milled by weight at a ball-milling speed of 1250 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a regulator.

[0125] The mass fraction of the lanthanum nitrate solution in this embodiment is 4.5%.

[0126] The production process of modified nano titanium dioxide in this embodiment is:

[0127] S11: preheating the nano-titanium dioxide at 57° C. for 12.5 minutes, and then treating it in a proton irradiation box for 12.5 minutes, with an irradiation power of 370 W. After the irradiation is completed, irradiated nano-titanium dioxide is obtained;

[0128] S12: stirring the irradiated nano titanium dioxide and the modified liquid at a weight ratio of 2:5 for modification treatment, filtering and drying after the stirring is completed to obtain modified nano titanium dioxide.

[0129] The stirring speed of the stirring modification treatment in this embodiment is 475 r / min, and the stirring time is 40 min.

[0130] The modified solution of this embodiment includes the following raw materials in parts by weight:

[0131] 3.5 parts of halloysite, 2 parts of nano silica sol, 5.5 parts of sodium silicate solution, 2.5 parts of flaky talc and 3 parts of dopamine hydrochloride solution.

[0132] The mass fraction of the sodium silicate solution in this embodiment is 3.5%; the mass fraction of the dopamine hydrochloride solution is 4.5%.

[0133] This embodiment also provides an anti-pilling high-density knitted fabric, which is produced by the production process of the anti-pilling high-density knitted fabric.

[0134] Comparative Example 1:

[0135] The difference from Example 3 is that no modified impregnating agent treatment is used.

[0136] Comparative Example 2:

[0137] The difference from Example 3 is that no regulator is added to the modified impregnating agent.

[0138] Comparative Example 3:

[0139] The difference from Example 3 is that no modified glass fiber is added in the preparation of the regulator.

[0140] Comparative Example 4:

[0141] The difference from Example 3 is that the modified glass fiber is directly replaced by the glass fiber raw material.

[0142] Comparative Example 5:

[0143] The difference from Example 3 is that no nano-mica powder liquid is added in the preparation of the regulator.

[0144] Comparative Example 6:

[0145] The difference from Example 3 is that no nano mica powder and sodium dodecylbenzene sulfonate solution are added to the nano mica powder liquid.

[0146] Comparative Example 7:

[0147] The difference from Example 3 is that no modified nano titanium dioxide is added.

[0148] Comparative Example 8:

[0149] The difference from Example 3 is that step S11 is not used in the preparation of modified nano-titanium dioxide.

[0150] Comparative Example 9:

[0151] The difference from Example 3 is that no modification liquid treatment is used in the preparation of modified nano-titanium dioxide.

[0152] The conventional performance tests of the products of Examples 1-3 and Comparative Examples 1-9 were conducted. The products were exposed to sunlight for 1 month and then washed 20 times to test the performance stability of the products under the conditions of exposure to sunlight and washing. The performance measurement results are shown in the following table:

[0153]

[0154] From Examples 1-3 and Comparative Examples 1-9, it can be concluded that the product of Example 3 of the present invention has excellent bursting strength, anti-pilling and anti-fouling properties under normal conditions, and the bursting strength, anti-pilling and anti-fouling properties of the product can achieve coordinated improvement, and the product has significant performance stability under conditions of exposure and washing;

[0155] It can be seen from Comparative Examples 1-9 and Example 3 that the performance of the product deteriorated significantly when the modified impregnating agent was not used. At the same time, when the modified impregnating agent was not added with a regulator or one of the modified nano titanium dioxide, the product performance also showed a significant deterioration trend. The modified impregnating agent obtained by the coordination of the two had the most significant product performance effect.

[0156] No modified glass fiber was added in the preparation of the regulator, the modified glass fiber was directly replaced by glass fiber raw material, no nano mica powder liquid was added in the preparation of the regulator, no nano mica powder and sodium dodecylbenzene sulfonate solution were added to the nano mica powder liquid, the S11 step was not used in the preparation of the modified nano titanium dioxide, and the modified liquid was not used in the preparation of the modified nano titanium dioxide. The performance of the product showed a trend of deterioration. The regulator obtained by combining the specific nano mica powder liquid and modified glass fiber of the present invention had the most significant product performance effect. At the same time, the modified nano titanium dioxide obtained by the specific S11 step of the present invention and the modified liquid treatment also had obvious product performance. In addition, the modified nano titanium dioxide was not treated with the modifying liquid in the preparation of the modified nano titanium dioxide, and the performance of the product also showed a relatively obvious trend of deterioration.

[0157] Based on the fact that the modified liquid has a significant impact on the performance of the product, further research is conducted on this.

[0158] Experimental Example 1:

[0159] The only difference from Example 3 is that halloysite is not added to the modified solution.

[0160] Experimental Example 2:

[0161] The only difference from Example 3 is that no sodium silicate solution is added to the modified liquid.

[0162] Experimental Example 3:

[0163] The only difference from Example 3 is that no dopamine hydrochloride solution is added to the modified liquid.

[0164] Experimental Example 4:

[0165] The only difference from Example 3 is that no flaky talc is added to the modified liquid.

[0166] Experimental Example 5:

[0167] The only difference from Example 3 is that no nano silica sol is added.

[0168] The conventional performance tests of the products of Experimental Examples 1-5 were conducted. The products were exposed to sunlight for 1 month and then washed 20 times to test the performance stability of the products under the conditions of exposure to sunlight and washing. The performance measurement results are shown in the following table:

[0169]

[0170] It can be seen from Experimental Examples 1-5 that the modified liquid does not contain halloysite, and the product performance is most significantly affected by the modified liquid, followed by the fact that no flaky talc is added. The modified liquid obtained by combining sodium silicate solution, dopamine hydrochloride solution and nano-silica sol with flaky talc and halloysite, and by the mutual coordination and synergy between the raw materials, has the most significant effect on the product performance. The raw materials in the modified liquid are indispensable, and other methods are used to replace them, but the effect is not as significant as that of the present invention.

[0171] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0172] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A production process for anti-pilling high-density knitted fabric, characterized in that: The following steps are involved: Step 1: Preparation of modified impregnating agent: (1) Weigh the raw materials according to weight: 2-5 parts of silane coupling agent KH560, 4-7 parts of regulator, 1-3 parts of yttrium nitrate solution, 2-4 parts of citric acid, 5-8 parts of sodium alginate solution and 3-5 parts of modified nano titanium dioxide; The production process of the regulator is: S01: Mix nano mica powder and chitosan solution with a mass fraction of 3-5% in a sodium dodecylbenzene sulfonate solution with a mass fraction of 5% to obtain a nano mica powder solution; The mass ratio of nano-mica powder, chitosan solution and sodium dodecylbenzene sulfonate solution is (2-5):3:(5-8); S02: 4-7 parts of glass fiber, 2-5 parts of lanthanum nitrate solution and 1-3 parts of carboxymethyl cellulose are mixed and ball-milled by weight, and then filtered and dried to obtain modified glass fiber. The ball-milling speed is 1500r / min and the ball-milling is performed for 1h; S03: 5-8 parts of nano-mica powder, 1-3 parts of silane coupling agent KH550 and 2-5 parts of modified glass fiber are mixed and ball-milled by weight at a ball-milling speed of 1000-1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain a regulator; The production process of the modified nano titanium dioxide is: S11: preheating the nano titanium dioxide at 55-60° C. for 10-15 minutes, and then treating it in a proton irradiation box for 10-15 minutes, with an irradiation power of 350-400 W. After the irradiation is completed, irradiated nano titanium dioxide is obtained; S12: stirring and modifying the irradiated nano titanium dioxide and the modified liquid in a weight ratio of 2:5, filtering and drying after the stirring is completed to obtain modified nano titanium dioxide; The modified liquid comprises the following raw materials in parts by weight: 2-5 parts of halloysite, 1-3 parts of nano silica sol, 4-7 parts of sodium silicate solution, 2-3 parts of flaky talc and 2-4 parts of dopamine hydrochloride solution; (2) Add silane coupling agent KH560, citric acid and yttrium nitrate solution to the sodium alginate solution, then add the regulator and modified nano titanium dioxide, continue to stir and mix thoroughly, and obtain a modified impregnating agent; Step 2: immersing the polyester filament and the spandex filament into a sufficient amount of a modified immersion agent for ultrasonic immersion treatment, and after the immersion is completed, taking out and drying to obtain the immersion-modified polyester filament and the immersion-modified spandex filament respectively; Step 3: The modified polyester filament and the modified spandex filament are used as warp and weft respectively, and the warp and weft are woven by a circular knitting machine to obtain a knitted fabric; the linear density of the warp is 9.8 tex, and the linear density of the weft is 8.5 tex; Step 4: Dry and shape the knitted fabric first, and then stretch and shape it on a shaping machine to obtain a high-density knitted fabric that is anti-pilling.

2. The production process of a high-density knitted fabric with anti-pilling properties according to claim 1, characterized in that: The ultrasonic power of the ultrasonic immersion treatment in step 2 is 400-500W, and the ultrasonic time is 20-30min; The drying and shaping time in step 4 is 20-25s, and the drying temperature is 135-145°C; the stentering and shaping temperature is 170-175°C, and the vehicle speed is 25-30m / min.

3. The production process of the anti-pilling high-density knitted fabric according to claim 1, characterized in that: The mass fraction of the yttrium nitrate solution is 2-5%; the mass fraction of the sodium alginate solution is 3-6%.

4. The production process of the anti-pilling high-density knitted fabric according to claim 1, characterized in that: The mass fraction of the lanthanum nitrate solution is 3-6%.

5. The production process of the anti-pilling high-density knitted fabric according to claim 1, characterized in that: The stirring speed of the stirring modification treatment is 450-550 r / min, and the stirring time is 35-45 min.

6. The production process of the anti-pilling high-density knitted fabric according to claim 1, characterized in that: The mass fraction of the sodium silicate solution is 2-5%; the mass fraction of the dopamine hydrochloride solution is 3-6%.

7. An anti-pilling high-density knitted fabric produced by the production process of an anti-pilling high-density knitted fabric according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Anti-pilling knitted cashmere and wool fiber product and preparation process thereof

    CN113005616A

  • Limonene-compound enzyme mercerizing shrink-proof and anti-pilling method for wool fabric

    CN116876204A